ANALISIS LINGKUNGAN SEBAGAI DASAR PERTIMBANGAN PENGAMBILAN KEPUTUSAN MANAGER DALAM MEMBUAT PRODUK - , Vindi Paputungan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Increasing in environment detriment at present day has very harmful side effect to human health. The industries have big responsible for this so they have to take big role to this problem, one solution by creating environmentally friendly products. The objectives of the study are to determine how environment analysis as managerial decision making basis in creating a product, are managers will creates environmentally friendly product that has more costly or conventional product that has negative effect to environment base on manager side of accounting and non accounting preferences. In this study, analysis was using laundry machine product as a sample. Data analysis was done using conjoint analysis for material cost features, in side tube design and machine (motor input). Quasi experimental design by questionnaire, consist experimental design or scene for attributes combination and sub attributes, was spreads to 60 people of MM UGM Yogyakarta. Non probability sampling was using in this study. The results were show that managers more interesting for produce environmentally friendly product and prefer from accounting side that is material cost attributes.